(3YeOI GdcJGH hYOI Phj GdCdHGH aj GdcJGHI hYed GdCMHGQ hGdGUHGZ hGdJPgjH hMd GdPgHs - (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s ((3GdcJHNGfI GdNOjhjI s)
(3ChdgG (B:s
(3HYO GdHSedI GdMeO ddg GdefYe GdeaVGd aEfj LeYJ aj gPG GdcJGH GdeSej HYeOI GdcJGHeeG jJYdb HGdcJGHI ef GdUfGFY s
(3BNQgG (B:s
(3aGFOI eGA CRQb jhbO Hg GdbfOjd jDNP NeSI OQGge QGSNJ hOQgejf hfUa fhTGOQ s
(3HgG fXGe GdJYbjHIs
(3fbdJ ef fSNI JjehQ Hcs
(3hHGdfSNI GVWQGH aj JQJjH GdChQGbs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs